Aspectos relevantes da gestão da qualidade e seus impactos nos resultados e nas melhorias na indústria hoteleira do turismo de negócios - Logiudice, Renato (2019)
In the last few decades, many organizations have implemented quality management systems to improve their performance. However, several technical and financial factors have been influencing the efficiency of the respective systems and thus preventing this improvement. It is precisely because of these difficulties that the present study originated, the objective of which was to propose a model that contemplates aspects relevant to quality management. The qualitative step identified 41 variables grouped into 5 factors. The subsequent quantitative stage, through a survey, involving the participation of 70 hotels of the economic categories, luxury and super focused on business tourism and located in the city of São Paulo. With the use of PLS ​​3.0 Smart MS software (Partial Least Squares) or Partial Least Squares, made possible through the perception of the general managers of hotels, the confirmation or otherwise of the assumptions referred to in the literature. The major factor of the study was to validate the conceptual model, which highlighted the important aspects that make up the requirements of a quality management system, including: the release of funds by investors to the improvement of processes as priorities, the evaluation and monitoring of suppliers and service providers, and the integration of employees into multifunctional activities.